Assessing the Impact of Air Pollution on Childhood Asthma Morbidity: How, When and What to Do - Burbank, Allison J. (Curr Opin Allergy Clin Immunol, 2018)
PURPOSE OF REVIEW: Exposure to air pollutants is linked with poor asthma control in children and represents a potentially modifiable risk factor for impaired lung function, rescue medication use, and increased asthma-related healthcare utilization. Identification of the most relevant pollutants to asthma as well as susceptibility factors and strategies to reduce exposure are needed to improve child health. RECENT FINDINGS: The current available literature supports the association between pollutants and negative asthma outcomes. Ethnicity, socioeconomic status, and presence of certain gene polymorphisms may impact susceptibility to the negative health effects of air pollution. Improved air quality standards were associated with better asthma outcomes. SUMMARY: The link between air pollution and pediatric asthma morbidity is supported by the recent relevant literature. Continued efforts are needed to identify the most vulnerable populations and develop strategies to reduce exposures and improve air quality.